1972
DOI: 10.1002/recl.19720910508
|View full text |Cite
|
Sign up to set email alerts
|

C‐nitroso compounds. Part XXIII: Cis/trans‐isomerisation of aliphatic azodioxy compounds (dimeric nitrosoalkanes)

Abstract: BYA mechanistic and kinetic study has been made of the cisltrans-isomerisation of cis-azodioxycyclohexane and cis-azodioxymethane in acetonitrile at temperatures, varying from 0-60". Cross-over and trapping experiments show that the isomerisation does not proceed by rotation around the N-N bond but exclusively via dissociation and recombination of free monomer molecules. Kinetic data indicate that the monomer molecules dimerize at low temperature by kinetic control chiefly to the cb-isomer. At elevated tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

1972
1972
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 36 publications
0
7
1
Order By: Relevance
“…The first kinetic study of the isomerization of dimers of nitrosoalkanes was published by Chaudhry and Gowenlock in 1968, but interpretation of their results was complicated by the competing formation of oximes by tautomerism . In 1972, Wajer and de Boer reported that the formation of oximes could be suppressed in acetonitrile, allowing them to study the cis–trans isomerization of the dimers of nitrosomethane and nitrosocyclohexane . Their kinetic data proved to be consistent with the mechanism of dissociation–association.…”
Section: Mechanism Of Dimerizationmentioning
confidence: 79%
See 1 more Smart Citation
“…The first kinetic study of the isomerization of dimers of nitrosoalkanes was published by Chaudhry and Gowenlock in 1968, but interpretation of their results was complicated by the competing formation of oximes by tautomerism . In 1972, Wajer and de Boer reported that the formation of oximes could be suppressed in acetonitrile, allowing them to study the cis–trans isomerization of the dimers of nitrosomethane and nitrosocyclohexane . Their kinetic data proved to be consistent with the mechanism of dissociation–association.…”
Section: Mechanism Of Dimerizationmentioning
confidence: 79%
“…128 In 1972, Wajer and de Boer reported that the formation of oximes could be suppressed in acetonitrile, allowing them to study the cis− trans isomerization of the dimers of nitrosomethane and nitrosocyclohexane. 129 Their kinetic data proved to be consistent with the mechanism of dissociation−association. Although this study demonstrated that the isomerization of azodioxides occurs preferentially by dissociation into nitroso monomers, the basis for this preference remained unclear.…”
Section: Cis−trans Isomerization Of Azodioxidesmentioning
confidence: 99%
“…C-nitrosobenzenes can exist in two different forms, as monomers or dimers (azodioxides). Broad literature is available on dimerization of nitrosobenzenes. Because the energy of an azodioxide (O)NN(O) bond is of the same order of magnitude as a hydrogen bond, its formation strongly depends on the conditions of the environment. In principle, dimers can be formed either in the crystal form or in solution by lowering temperature. , Previous studies revealed that if the molecules are favorably oriented in the crystal lattice with their nitroso groups properly oriented in the vicinity then they would readily form azodioxides in crystals. , Such dimers can undergo photodissociation to monomers in crystals only at low temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…The liquid-state one-dimensional 1 H and 13 C NMR spectra (600.13 MHz for 1 H, 150.90 MHz for 13 C) were measured in CDCl 3 on a Bruker AV600 spectrometer at room temperature. Chemical shifts, in ppm, were referred to tetramethylsilane (TMS) as the internal standard.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…In solid state, C -nitroso compounds are usually present as dimers, and in the solution there is an equilibrium between monomers and dimers. In aromatic C -nitroso compounds at room temperature the equilibrium is usually shifted toward monomers, and Z - or E -dimers can be observed only at low temperatures. Different behavior has been observed for 2-nitrosopyridines, where dimers can coexist with monomers even at room temperature.…”
Section: Introductionmentioning
confidence: 99%